Presence of s-Wave Pairing in Josephson Junctions Made of Twisted Ultrathin Bi_{2}Sr_{2}CaCu_{2}O_{8+x} Flakes - Yuying Zhu (American Physical Society, 2021)
Since the discovery of high-temperature superconductivity in cuprates, Josephson junction based phase-sensitive experiments are believed and used to provide the most convincing evidence for determining the pairing symmetry. Regardless of different junction materials and geometries used, quantum tunneling involved in these experiments is essentially a nanoscale process, and thus, actual experimental results are extremely sensitive to atomic details of the junction structures. The situation has led to controversial results as to the nature of the pairing symmetry of cuprates: while in-plane junction experiments generally support d-wave pairing symmetry, those based on out-of-plane (c-axis) Josephson junctions between two rotated cuprate blocks favor s-wave pairing. In this work, we revisit the c-axis experiment by fabricating Josephson junctions with atomic-level control in their interface structure. We fabricate over 90 junctions of ultrathin Bi_{2}Sr_{2}CaCu_{2}O_{8+x} (BSCCO) flakes by state-of-the-art exfoliation technique and obtain atomically flat junction interfaces in the whole junction regions as characterized by high-resolution transmission electron microscopy. Notably, the resultant uniform junctions at various twist angles all exhibit a single tunneling branch behavior, suggesting that only the first half of a unit cell on both sides of the twisted flakes is involved in the Josephson tunneling process. With such well-defined geometry and structure and the characteristic single tunneling branch, we repeatedly observe Josephson tunneling at a nominal twist angle of 45°, which is against the expectation from a purely d-wave pairing scenario. Our results strongly favor the scenario of a persistent s-wave order parameter in the junction.